What are they waiting for?—Tethered agonism in G protein-coupled receptors. (June 2016) - Schöneberg, Torsten; Kleinau, Gunnar; Brüser, Antje
Graphical abstract: Abstract: In classical pharmacology agonists bind to their respective receptors by specific interaction and induce structural changes followed by cellular responses. However, some G protein-coupled receptor (GPCRs), such as rhodopsin and protease-activated receptors (PARs), have their agonists already covalently bound and are parts of the receptor proteins, respectively. Recent studies add adhesion GPCRs and glycoprotein hormone receptors (GPHRs) to the group of GPCRs activated by integral agonists. In contrast to rhodopsin and PARs, adhesion GPCRs and GPHRs exhibit large ectodomains (ECDs) which bind a number of different proteins and other extracellular molecules. It seems that these large size ECDs are required to integrate a multitude of extracellular signals, such as protein ligand binding, cell-cell contacts and even mechanical forces, into uniform intracellular signals. Upon extracellular ligand binding, the intramolecular agonist of those receptors is exposed or isomerizes and induces structural changes in the 7-transmembrane helix domain triggering G-protein activation. The existence of activating structures integrated in receptor molecules challenges our current pharmacological definition of an agonist. We summarized and discussed the specifics of tethered agonist pharmacology which add a number of new features of the already broad signaling abilities of GPCRs and may find useful applications in designer GPCRs.